Efeito da espessura de camada do revestimento galvannealed (GA) sobre a resistência à corrosão de um aço ao boro conformado a quente - Renata da Costa Moreira (2019)
The demand for car weight reduction has increased the use of high-strength steels, due to the need to reduce fuel consumption and improvement of the safety conditions. In order to obtain parts of complex geometries, a process was developed in which the stamping occurs in high temperature, called hot stamping (HS).The Zn-Fe (GA) coated boron steels developed by Usiminas have been showing good results in the tests performed. In this study the corrosion resistance of three GA coating thicknesses (6 µm, 8 µm and 11 µm per side) after the hot stamping process was evaluated. Independent of the type of corrosion test performed, as much larger the initial coating layer (before hot stamping), the lower will be the corrosion advance and/or paint peeling. The Zinc acted as an anode in the system created and was corroded rather than iron. The greater the amount of zinc, the greater the protective capacity and the longer it will take for substrate corrosion to begin.